The Dialectics of Resistance: Lebanese National Identity Formation Through the Prism of Anti-Occupation Struggle, 1978-2000 - Badawi, Habib (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study explores the formation of Lebanese national identity through anti-occupation resistance from 1978 to 2000, employing historical methodology with a multidisciplinary approach. It examines how resistance shaped Lebanon's collective consciousness, challenged sectarian divisions, and redefined its role regionally and globally. Using a combination of collective memory (Halbwachs), nationalism (Anderson), critical geopolitics (Toal), cultural trauma (Alexander), postcolonial theory (Said and Bhabha), and social movement theory (Tarrow and McAdam), the research analyzes the transformation of fear into resilience and the impact of the 2000 Israeli withdrawal on identity formation. The study highlights the dual nature of resistance culture, both unifying and challenging, and critically examines how shared trauma influences national identity. It addresses generational shifts in perceptions of resistance and focuses on long-term identity implications, offering a forward-looking perspective on Lebanon’s ongoing development. By integrating historical methods with insights from nationalism, social movements, and cultural studies, the research situates Lebanon’s resistance within broader regional and global dynamics, providing insights into asymmetric warfare and the role of non-state actors in international relations.